Struktur Naratif Teras Berita Daring Kasus-Kasus Kekerasan Seksual: Analisis Wacana Kritis Model Roger Fowler - Fanesha Widya Pramesti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jember, 2026)
Narrative structure as a way of arranging language elements in a text for a certain perspective has an important role in directing the reader's gaze in understanding the news presented. Sexual violence cases are cases that are often reported in online mass media. News portals that are included in online mass media have a diversity of languages in conveying news and often contain certain ideologies that can be analyzed through the perspective of critical discourse analysis of the Roger Fowler model. This research aims to describe the selection of vocabulary and the use of grammar on the news core of sexual violence cases built by online mass media. This research uses a qualitative research design with a descriptive research type. The data source in this study is a digital document in the form of news articles on online mass media news portals, namely Tempo.co, Liputan6.com, and Okezone.com, which contain news about sexual violence cases. The technique that used to collect data is the documentation technique. Data analysis techniques consist of data reduction, data display, verification and conclusions drawing. The research procedure includes three stages, namely preparation stage, implementation stage, and completion stage. The results of the study found that (1) the vocabulary selection that used by online mass media, especially the three news portals studied, including classification vocabulary, restrict the views, discourse contestation, and marginalization which are often used to conceal the perpetrator, excommunicate the victim, and there is an ideology behind it. (2) the grammar usage by online mass media, especially the three news portals studied, including of passive voice usage, nominalization, transitive model, intransitive model, and relational model that shows that the linguistic structure used by the media is not neutral. For future research candidates in related fields, thus research can be developed on aspects that have not been reached in this study and can expand the study object by analyzing the news core from various other online news portals.
FINALISASI oleh Arif 2026 Juni 11
Keywords: Narrative Structure; Vocabulary; Grammar; Marginalization; Sexual Violence